Enhancing Motor Brain Activity Improves Memory for Action Language: A tDCS Study. (2nd November 2020) - Vitale, Francesca; Padrón, Iván; Avenanti, Alessio; de Vega, Manuel
Abstract: The embodied cognition approach to linguistic meaning posits that action language understanding is grounded in sensory–motor systems. However, evidence that the human motor cortex is necessary for action language memory is meager. To address this issue, in two groups of healthy individuals, we perturbed the left primary motor cortex (M1) by means of either anodal or cathodal transcranial direct current stimulation (tDCS), before participants had to memorize lists of manual action and attentional sentences. In each group, participants received sham and active tDCS in two separate sessions. Following anodal tDCS (a-tDCS), participants improved the recall of action sentences compared with sham tDCS. No similar effects were detected following cathodal tDCS (c-tDCS). Both a-tDCS and c-tDCS induced variable changes in motor excitability, as measured by motor-evoked potentials induced by transcranial magnetic stimulation. Remarkably, across groups, action-specific memory improvements were positively predicted by changes in motor excitability. We provide evidence that excitatory modulation of the motor cortex selectively improves performance in a task requiring comprehension and memory of action sentences. These findings indicate that M1 is necessary for accurate processing of linguistic meanings and thus provide causal evidence that high-order cognitive functions are grounded in the human motor system.